Malaria vectors in the changing environment of the southern Punjab, Pakistan - Klinkenberg, Eveline; Konradsen, Flemming; Herrel, N.; Mukhtar, M.; Hoek, Wim van der; Amerasinghe, Felix P. (2004)
The Pakistani Punjab experienced several devastating malaria epidemics during the twentieth century. Since the 1980s, however, malaria has been at a low ebb, while in other areas of Pakistan and neighbouring India malaria is on the increase. This raises the question of whether transmission in the Pakistani Punjab may have been in uenced by a change in vector species abundance or composition, possibly induced by environmental changes. To investigate this question, routinely-collected government entomological data for the period 1970 to 1999 for the district of Bahawalnagar, in the Indus Basin irrigation system in the southern Punjab, was analysed. Our ndings suggest that Anopheles stephensi has increased in prevalence and became more common than A. culicifacies during the 1980s. This shift in species dominance may be due to the large-scale ecological changes that have taken place in the Punjab, where irrigation-induced waterlogging of soil with related salinization has created an environment favourable for the more salt-tolerant A. stephensi. Some biotypes of A. stephensi are suspected of being less ef cient vectors and, therefore, the shift in species dominance might have played a role in the reduced transmission in the Punjab, although further research is needed to investigate the effect of other transmission-in uencing factors.